2008
DOI: 10.1007/s11250-008-9190-x
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Oestrus ovis infestations in sheep in Kars province of north-eastern Turkey

Abstract: This study was carried out to determine the prevalence of cavical myiasis caused by Oestrus ovis larvae in sheep of Kars province of north-eastern part of Turkey. From 30 to 35 sheep heads (total of 387) were examined every month regularly for O. ovis larvae during 12 months. Of 387 heads, 156 (%40.3) were infested with O. ovis larvae.. The prevalence of nasal myiasis was 54.3% in spring, 41% in summer, 28% in fall, and 38.9% in winter. The differences among seasons were significant statistically (P<0.05). Inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
34
6
4

Year Published

2009
2009
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(57 citation statements)
references
References 18 publications
13
34
6
4
Order By: Relevance
“…The larvae collection was similar to those recorded by Arslan et al (2009) andSilva (2013), who both indicate that the numbers of L1 were much less than L2 and L3. Furthermore, they each conclude that most of the L3 larvae in the early summer, probably as a survival strategy, given that the larvae did not complete their cycle due to unfavorable weather conditions (Tabouret et al 2001).…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…The larvae collection was similar to those recorded by Arslan et al (2009) andSilva (2013), who both indicate that the numbers of L1 were much less than L2 and L3. Furthermore, they each conclude that most of the L3 larvae in the early summer, probably as a survival strategy, given that the larvae did not complete their cycle due to unfavorable weather conditions (Tabouret et al 2001).…”
Section: Discussionsupporting
confidence: 83%
“…Although Arslan et al (2009) found that animals older than three years showed a higher prevalence (52.4%), this is consistent with the direct relationship between age and risk of infection over time. In sheep under 1 year, the percentage of infection was lower, coinciding with the distributions observed for Arslan et al (2009) and Silva et al (2013). It could be considered that in southern Chile the infection of lambs is late because the optimal environmental conditions for the larval lay process of female flies begins around spring probably.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The prevalence of O. ovis infestation (13.7%) in this study was lower than those reported in similar studies carried out in other countries such as France, where 65% of sheep was infested with O. ovis larvae (YILMA; DORCHIES, 1991); or in Sicily, with 55.8% of prevalence (CARACAPPA et al, 2000); and Turkey, with 40.6% (ARSLAN et al, 2009). Higher prevalence was also observed in other Brazilian studies: 85.4% in the south region of the country in sheep exposed to natural infestation for one year (RIBEIRO et al, 1990) and 50% prevalence in tracer sheep in Botucatu, State of São Paulo, Brazil (SILVA et al, 2012).…”
Section: Discussioncontrasting
confidence: 76%
“…The difference between results may be explained in part by the fact that in Bagé, the animals were exposed to O. ovis infestation for a longer period of time (from one month to one year), while in the present experiment the sheep were exposed for just 28 days. Moreover, other factors may have influenced the O. ovis epidemiology, such as the climatic conditions of each region, size of sheep flock and management, which can result in a variable prevalence, as demonstrated by numerous studies conducted in slaughterhouses in different countries (YILMA;DORCHIES, 1991;ABO-SHEHADA et al, 2000;SCALA et al, 2002;ALCAIDE et al, 2003;ARSLAN et al, 2009;SHOORIJEH et al, 2009).…”
Section: Discussionmentioning
confidence: 99%